Pengaruh Brand Image, Kualitas Produk dan Pelayanan Purna Jual terhadap Keputusan Pembelian Honda Supra X 125 pada PT. Tunggul Sakti Sejahtera - Titus Laksa Gumilang; Wahyu Hidayat; Sri Suryoko (Universitas Diponegoro, 2013)
This research was conducted to determine the effect of brand image, product quality and after-sales service on purchase decisions Honda Supra X 125 at PT Tunggul Sakti Sejahtera. This study used an explanatory approach to research on 100 respondents. Sampling is done by accidental sampling technique. The data obtained were analyzed qualitatively and quantitatively. Determination test results showed that 32.7% of decision variables can be explained by the variable purchase brand image, 60.5% purchase decision variables can be explained by the variable quality of the product, 40.8% purchase decision variables can be explained by variable after-sales service. 61.2% purchase decision variables can be explained by the brand image, product quality and after-sales service. The results of hypothesis testing (t test) that brand image has a positive and significant impact on purchasing decisions, The quality of the product has a positive and significant impact on purchasing decisions. Furthermore, after-sales service has a positive and significant impact on purchasing decisions. Hypothesis test (F test) the brand image, product quality and after-sales services together - each has a positive influence and significant impact on purchasing decisions. So that concluded the three variables, both individually and collectively - each has a positive and significant impact on the purchase decision of Honda Supra X 125 at PT Tunggul Sakti Sejahtera Semarang.